A measure of tourist responsibility - Dias, Á.; Aldana, I.; Pereira, L.; Lopes da Costa, R.; António, N. (Sustainability, 2021)
In a post-pandemic context, destinations are questioning mass tourism, and are focusing on more sustainable segments, looking for more responsible tourists. This requires obtaining relevant information to assess what kind of tourists visit the destination and, at the same time, to monitor changes in tourists’ behavior and attitudes. This study aims to respond to this challenge by creating a measure to assess the tourist’s responsibility. Using a scale development method, a sequential mixed-method approach is conducted to identify scale dimensions and items. An initial qualitative approach is implemented for item generation using focus group and face-to-face interviews. Then, a second study based on a survey is conducted for exploratory factor analysis. A third study, also based on a survey is performed to obtain a new sample for confirmatory factor analysis. Findings show two dimensions: civic responsibility and philanthropic responsibility, allowing an understanding of how tourists can act responsibly in destinations without compromising the ecological footprint on the planet. Theoretical and managerial implications are discussed.